2000
DOI: 10.1017/s0031182099005351
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Echinococcus multilocularis in urban red foxes (Vulpes vulpes) and voles (Arvicola terrestris) in the city of Zürich, Switzerland

Abstract: Over a period of 26 months from January 1996 to February 1998, 388 foxes from the city of Zürich, Switzerland, were examined for intestinal infections with Echinococcus multilocularis and other helminths. The prevalence of E. multilocularis in foxes sampled during winter increased significantly from 47% in the urban to 67% in the adjacent recreational area, whereas prevalence rates of other helminths were similar in both areas. Seasonal differences in the prevalence of E. multilocularis were only found in urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
276
9
14

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 306 publications
(325 citation statements)
references
References 10 publications
26
276
9
14
Order By: Relevance
“…This may be due to parasite-induced host immunity to reinfection. This phenomenom was also observed in other studies (Hofer et al, 2004) and was also seen in dogs infected with E. granulosus (Torgerson et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…This may be due to parasite-induced host immunity to reinfection. This phenomenom was also observed in other studies (Hofer et al, 2004) and was also seen in dogs infected with E. granulosus (Torgerson et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The same trend was observed in Switzerland: Zürich (Hegglin et al, 2007;Hofer et al, 2000) and Geneva (Fischer et al, 2005). The first report of an urban cycle for E. multilocularis concerned the city of Zürich.…”
Section: Gradient Of Infection and Urbanisation Levelsupporting
confidence: 67%
“…The analysis of the effect of urbanisation level, year, season, age class and sex have shown that urbanisation only explained fox infection. Other studies have revealed a seasonal prevalence in an urban area with higher rate in winter for young males (Hofer et al, 2000) and more pronounced variation along the urbanisation gradient in juveniles foxes than in adult foxes (Hegglin et al, 2007). In our study urban positive cases were juveniles males.…”
Section: Gradient Of Infection and Urbanisation Levelsupporting
confidence: 52%
“…The infection pressures reported for E. multilocularis assume that infection pressure is constant throughout the year which is unlikely. In Switzerland for example, differences in prevalences have been suggested between foxes sampled in the winter and the summer (Hofer et al, 2000;Stieger et al, 2002;Hegglin et al, 2007). Studies are being undertaken to resolve the issues of seasonal transmission in Kyrgyzstan.…”
Section: Discussionmentioning
confidence: 99%